2015
DOI: 10.1371/journal.pone.0128598
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a Bioinformatics Microarray Analysis Workflow for a Toxicogenomic Study in Rainbow Trout

Abstract: Sex steroids play a key role in triggering sex differentiation in fish, the use of exogenous hormone treatment leading to partial or complete sex reversal. This phenomenon has attracted attention since the discovery that even low environmental doses of exogenous steroids can adversely affect gonad morphology (ovotestis development) and induce reproductive failure. Modern genomic-based technologies have enhanced opportunities to find out mechanisms of actions (MOA) and identify biomarkers related to the toxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…In addition, our results showed that genes related to several metabolic‐related processes, such as the cellular metabolic process, the primary metabolic process, and the organic substance metabolic process were significantly enriched in embryos treated with nsPEF and E 2 . Previous transcriptomic and/or proteomic studies reported that the synthetic estrogen, ethynylestradiol, affected various metabolic processes in teleost fishes such as rainbow trout ( Oncorhynchus mykiss ) (Depiereux et al, ) and zebrafish ( D. rerio ) (De Wit et al, ). Moreover, previous surveys using medaka fish have also demonstrated that approximately one‐quarter of the up‐ or downregulated genes were categorized as “metabolism” in the larval stages when exposed to 100 ng l –1 E 2 for 7 days, as determined via a microarray analysis (Mizukami‐Murata & Kishi‐Kadota, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed that genes related to several metabolic‐related processes, such as the cellular metabolic process, the primary metabolic process, and the organic substance metabolic process were significantly enriched in embryos treated with nsPEF and E 2 . Previous transcriptomic and/or proteomic studies reported that the synthetic estrogen, ethynylestradiol, affected various metabolic processes in teleost fishes such as rainbow trout ( Oncorhynchus mykiss ) (Depiereux et al, ) and zebrafish ( D. rerio ) (De Wit et al, ). Moreover, previous surveys using medaka fish have also demonstrated that approximately one‐quarter of the up‐ or downregulated genes were categorized as “metabolism” in the larval stages when exposed to 100 ng l –1 E 2 for 7 days, as determined via a microarray analysis (Mizukami‐Murata & Kishi‐Kadota, ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial microarray analysis workflow [ 24 ] was adapted to handle another type of microarray platform (dataset 2) and to fit with the meta-analysis scheme and work hypothesis. Briefly, this workflow includes (i) the analysis of pre-treated data by (ii) ANOVA analysis followed by Scheffe’s post hoc pairwise comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Data analyses were performed using the R statistical software version 2.15.3 available on the R-Project website ( http://cran.r-project.org ) and a set of packages available in the Bioconductor repository ( http://www.bioconductor.org ). This methodology used for the first dataset [ 24 ] was also applied to re-analyse the dataset 2. Therefore, brief descriptions and specificities related to this dataset analysis are provided below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations